Performance comparison between NoSQL (RethinkDB) and MySQL database replication from master to slave in big data - Dildar Hussain,; Mohammad Omar,; Khairol Amali Ahmad,; Ja’afar Adnan,; Khaleel Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2021)
When database is stored in one computer or server, certain issues related to disaster (in terms of natural or un-natural) problem may arise with reference to geographical connection and geographical distribution of servers. Here, replication feature plays an important role. There were many techniques and methodologies for geographically distributed servers, but the problem was of one master. When an authorized user updates his database on a client database server then this client database server updates his master database server and at last, the master database server updates all its client’s database servers. The described process is called database replication. In this process, there are several main parameters that are important, i.e., bandwidth, memory, and processor time. In this paper, the analysis is focused on comparing which database (NoSQL family-RethinkDB and MySQL) utilize how much memory, processor, and time during replication of database from client to master.